Stress concentration and failure analysis for materials with application in aerospace engineering - Zhao, Xing. (2012)
In engineering structures and materials, stress concentrations around different notches cause the stress level much higher than the designed stress. Particularly when there are cracks initiated from those high-stress concentrated areas, the mechanical strength of those structures and materials becomes much weaker. Failure will be caused accordingly. The current project investigates various stress concentration and fracture problems which are widely encountered in aerospace structures and materials. Parametric study of the stress concentration factors and stress intensity factors has been conducted. Finite element software Abacus/CAE 6.9 is used for the numerical simulation. The procedure is based on the Abacus/CAE 6.9’s step: Part->Property->Assembly->Step->Interaction->Load->Mesh->Job->Visualization. This analysis method is conducted to study the stress distribution and stress intensity factors onto the crack-tip with crack length. Different crack geometries (cracks initiated from various notches such as triangle; semi-circle and semi-ellipse) are studied, by varying related parameter.